2021
DOI: 10.3390/biomedicines9111654
|View full text |Cite
|
Sign up to set email alerts
|

Biological Activity Evaluation and In Silico Studies of Polyprenylated Benzophenones from Garcinia celebica

Abstract: This study aimed to isolate polyprenylated benzophenones from the rootbark of Garcinia celebica and assess their activities in vitro and in silico. The antioxidant activity was evaluated by the DPPH, ABTS, and FRAP methods. The cytotoxicity was evaluated against HeLa, MCF-7, A549, and B16 cancer cell lines. The antiplasmodial activity was performed against the chloroquine-sensitive Plasmodium falciparum strain 3D7. Molecular docking was analyzed on alpha-estrogen receptor (3ERT) and P. falciparum lactate dehyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 55 publications
(86 reference statements)
0
17
0
2
Order By: Relevance
“…Moreover, GBL was nontoxic towards normal ovarian epithelial cells indicating that it exhibits some cytotoxic specificity. Some previous studies revealed that several polyprenylated benzophenones found in the Clusiaceae family have potent biological activities, especially cytotoxicity against cancer cell lines [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, GBL was nontoxic towards normal ovarian epithelial cells indicating that it exhibits some cytotoxic specificity. Some previous studies revealed that several polyprenylated benzophenones found in the Clusiaceae family have potent biological activities, especially cytotoxicity against cancer cell lines [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Benzophenones were reported to inhibit cancer cell lines through various mechanisms of action, including apoptosis, cell cycle arrest, and endoplasmic reticulum response [ 32 ]. For instance, guttiferone E, xanthochymol, and guttiferone H isolated from Garcinia xanthochymus have shown to induce the cell cycle arrest, caspase activation associated with interference of the mitochondrial membrane potential, and the activation of the endoplasmic reticulum stress [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DPPH (1,1-diphenyl-2-picrylhydrazyl) radicals scavenging activity was determined as previously described. 4 33.3 μL of each extract at different concentrations (159.73–4.99 μg mL −1 ) was added to 1 mL of DPPH 6.0 × 10 −5 M and the mixture were incubated at 37 °C for 20 minutes in dark room. The absorbance was measured at 517 nm using UV-visible Spectrophotometer (Thermo Fisher Scientific, USA) with three replications.…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, cancer is one of the main causes of death in the world with about 9.6 million deaths were recorded in 2018. 4 Cancer is caused by abnormal growth of cells due to various gene mutations and unstoppable cell division. An effort in searching of effective cancer drugs becomes main research focus, as the number of new cancer cases increases per year.…”
Section: Introductionmentioning
confidence: 99%